Upconversion nanoparticles as a contrast agent for photoacoustic imaging in live mice - Maji, Swarup Kumar (2014)
An inclusion complex of NaYF4:Yb3+,Er3+ upconversion nanoparticles with α-cyclodextrin in aqueous conditions exhibits luminescence quenching when excited at 980 nm. This non-radiative relaxation leads to an unprecedented photoacoustic signal enhancement. In vivo localization of α-cyclodextrin-covered NaYF4:Yb3+,Er3+ is demonstrated using photoacoustic tomography in live mice, showing its high capability for photoacoustic imaging.